O Prefață uitată a lui Paul Zarifopol - Andreea Mironescu (Revista de Istorie și Teorie Literară)
This article has two parts. The first one provides some pieces of information about the introductory essay published by Paul Zarifopol in the opening of his anthology Vedenii/ Phantasmagoria (1926), containing several fantastic novels translated by Zarifopol himself into Romanian. Since this essay, entitled simply Prefață / Preface, is missing from all the editions of Zarifopol’s work, the second part of the article reproduces it end-to-end. The Preface is also an important essay by Zarifopol on the aesthetical experience, alongside more notorious texts such as Recapitulări/ Iterations (1930) or În planul esthetic/ The Aesthetical Level (1933).